2016
DOI: 10.1016/j.epag.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of viral acute lower respiratory tract infection in hospitalized infants using real-time PCR

Abstract: Introduction: Acute lower respiratory tract infection in children causes significant morbidity in the developing countries. Documentation of virus infection using PCR and clinical characteristics of patients affected with viral pneumonia are reviewed in this study. Methods: 51 children less than three years admitted to the Pediatric Hospital, Cairo University with viral pneumonia were included. All patients had undergone nasopharyngeal aspirate for PCR viral detection. Results: A total of 51 cases were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…JBI quality assessment tools were applied and all included studies satisfied the required level of methodological quality. The minimum and maximum sample sizes utilized were 51 [ 17 ] and 9969 [ 18 ], respectively. Considering the number of studies included from sub-regions of Africa, 24 reports were from Northern, 23 from Eastern, 18 from Southern, 16 from Western, and six from Middle Africa, while one study presented data from three African sub-regions ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…JBI quality assessment tools were applied and all included studies satisfied the required level of methodological quality. The minimum and maximum sample sizes utilized were 51 [ 17 ] and 9969 [ 18 ], respectively. Considering the number of studies included from sub-regions of Africa, 24 reports were from Northern, 23 from Eastern, 18 from Southern, 16 from Western, and six from Middle Africa, while one study presented data from three African sub-regions ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The inter‐rater agreement for study selection was high ( κ = 0.81). Finally, 66 full texts including 67 studies were included (one paper included two studies) …”
Section: Resultsmentioning
confidence: 99%
“…Abdel-Moneim et al ( 2016) used newly developed primers to increase the sensitivity of the PCR test for HBoV detection. Using these novel primers, the prevalence of HBoV was 56.8%, which significantly differs from previous and further studies conducted in Egypt, which found prevalence values of 22%, 10% and 18.2% respectively [12,13,17]. Abdel-Moneim et al explained that the high rate of prevalence of HBoV-1 was reported because of a potential nosocomial pathogen among pediatric care units.…”
Section: Discussionmentioning
confidence: 63%